Direct solution of uncertain bratu initial value problem - N. R. Anakira; A. H. Shather; A. F. Jameel; A. K. Alomari; A. Saaban (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, an approximate analytical solution for solving the fuzzy Bratu equation based on variation iteration method (VIM) is analyzed and modified without needed of any discretization by taking the benefits of fuzzy set theory. VIM is applied directly, without being reduced to a first order system, to obtain an approximate solution of the uncertain Bratu equation. An example in this regard have been solved to show the capacity and convenience of VIM.